Cost-effectiveness of Paxlovid in reducing severe COVID-19 and mortality in China - Zhang, Weina; Li, Lanfang; Zhou, Zhen; Liu, Qiao; Wang, Guan; Liu, Dan (Frontiers in Public Health, 2023)
Objectives To assess the cost-effectiveness of Paxlovid in reducing severe COVID-19 and its associated morality, and to investigate the affordable price of Paxlovid in China. Material and Methods Using a Markov model, two interventions by Paxlovid prescription (with and without prescription) were compared in terms of COVID-19-related clinical outcomes and economic loss. COVID-related costs were collected from the societal perspective. Effectiveness data were obtained from literature. The primary outcomes were total social cost, disability adjusted life-years (DALYs) and net monetary benefit (NMB). Scenario analyses were performed to investigate the affordable price of Paxlovid in China. Deterministic sensitivity analyses (DSA) and probabilistic sensitivity analysis (PSA) were performed to verify the model robustness. Results: Compared with the non-Paxlovid cohort, the NMBs of the Paxlovid cohort were only higher in the subgroup of patients aged over 80 years old, regardless of their vaccination status. Our scenario analysis found that, the price ceiling of Paxlovid/box for it to be cost-effective was RMB 8,993 (8,970-9,009) in those aged over 80 years old who were not vaccinated, which is the highest; and was RMB 35 (27-45) in those aged 40-59 years old who were vaccinated, which is the lowest. Sensitivity analyses found that the incremental NMB for the vaccinated people aged over 80 years was most sensitive to the efficacy of Paxlovid and the cost-effectiveness probability of Paxlovid increased with its decreased price. Conclusion: Under the current marketing price of Paxlovid/box (RMB 1,890), using Paxlovid was only cost-effective in people aged over 80 years old regardless of their vaccination status.